1994
DOI: 10.1210/jcem.79.6.7527406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 17 beta-estradiol on circulating adhesion molecules.

Abstract: The effects of 17 beta-estradiol (E2) on the serum levels of the circulating endothelial-leukocyte, intercellular, and vascular adhesion molecules [ELAM-1, ICAM-1 (CD54), and VCAM-1] were evaluated in healthy male volunteers after single im injection of 10 mg E2 valerate. In addition, a time course of the effects of E2 on circulating adhesion molecules (AMs), cortisol serum levels, differential blood counts, and surface expression of the lymphocyte function-associated antigen-1 (CD11a/CD18), CD3, CD4, CD19, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 40 publications
1
23
1
Order By: Relevance
“…Sex differences for E-selectin have been described in adults previously. 38 As opposed to our original hypothesis, hsCRP did not correlate with IMT or FMD in our study. This is in slight contrast to a study of Järvisalo et al, 39 in which CRP was an independent predictor of brachial FMD in healthy children, and also to the data of Whincup et al, 40 who observed a fairly weak inverse association of CRP with arterial distensibility in 249 boys but not in 222 girls 13 to 15 years old.…”
Section: Discussioncontrasting
confidence: 99%
“…Sex differences for E-selectin have been described in adults previously. 38 As opposed to our original hypothesis, hsCRP did not correlate with IMT or FMD in our study. This is in slight contrast to a study of Järvisalo et al, 39 in which CRP was an independent predictor of brachial FMD in healthy children, and also to the data of Whincup et al, 40 who observed a fairly weak inverse association of CRP with arterial distensibility in 249 boys but not in 222 girls 13 to 15 years old.…”
Section: Discussioncontrasting
confidence: 99%
“…4 We deemed that detecting a 20% decrease would be of clinical relevance as most of the cardiovascular diseases including hypertension and diabetes are associated with a 20% to 30% increase in cAM. 10,11,13,23,24 Based on previous findings on the intrasubject variability of cAM 25,26 and the expected standard deviation we calculated 27 that 10 subjects were required in our study. In addition, 82 healthy subjects served as control subjects.…”
Section: Methodsmentioning
confidence: 99%
“…29,30 All soluble adhesion molecules were determined by commercially available enzyme immunoassays for soluble E-selectin, ICAM-1, and VCAM-1 (R&D Systems, Oxfordshire, England) as described previously. 25,26 Glucose, glycosylated hemoglobin (HbA 1c ), microalbuminuria, and serum lipids were determined as described previously. 14,31,32 Statistics As data were nonnormally distributed, nonparametric statistics were applied.…”
Section: Methodsmentioning
confidence: 99%
“…The nonlipid effects of estrogen that may contribute to the cardioprotection observed in humans include the following: effects on endothelial metabolism (8,9), myocardial conductance, hemostatic factors (10,11), vascular tone and reactivity (12), intimal cell proliferation (13,14), Lp(a) levels (15), expression of adhesion molecules (16), platelet aggregation (17), LDL oxidation (18, 19), inflammatory cytokine expression (20,21), and extracellular matrix synthesis. Additionally, estrogen might affect arterial wall calcification (22), the formation of unstable plaque and the generation of occlusive thrombi (4).…”
mentioning
confidence: 99%